Media coverage of environmental issues in Bangladesh and its role in influencing policy and action / Nerun N Yakub - Yakub, Nerun N (Faculty of Communication and Media Studies (FCMS), 1993)
Bangladesh's policy makers, did not even incorporate the word 'environment' in its national development plans prior to 1990. After the two major floods in Bangladesh-1987 and 1988- got environmentalists linking deforestation, hydrological interventions, global warming, unwise land use and other natural and man-made phenomena with our disasters, decision-makers were stirred into considering a national environment policy, to guide development, resource utilisation and resource replenishment. Even then in the country's fourth and latest plan-which was being drafted sometime after the great floods, -environment gets only a token mention. And the draft environment policy was not worked out until 1991. But its fate is yet to be decided. In the second year of the Decade of Environment, Bangladesh finds itself still grappling with what its environment policy should incorporate and emphasise, leave out or underplay. The Ministry of Industry is reportedly resisting the national environment policy and action plan on the grounds that its adoption would retard industrialsation and economic recovery.